Oxygen scavenging activity of smart colophony microcapsules containing nitrite corrosion inhibitors for steel reinforced concrete - Ress, Jacob; Martin, Ulises; Bastidas, David M. (Frontiers in Materials, 2022)
In this study, the electrochemical performance of microcapsules (MCs) containing NaNO2 corrosion inhibitors for steel reinforcements was studied in 0.6 M chloride contaminated simulated concrete pore solutions (SCPS) with varying pH for a period of 28 days. The corrosion inhibition was studied by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The polarization results for the MC samples showed improved corrosion resistance, with an icorr of 2.54 ×10−6 A/cm2 after 28 days exposure in SCPS. Oxygen scavenging activity from the MCs was observed by reduced cathodic kinetics, displaying decreased cathodic exchange current densities of 2.66 ×10–8 A/cm2, thus imparting cathodic inhibition in conjunction with anodic corrosion inhibitors. The microcapsules additionally displayed improvement over free NaNO2 inhibitors after sufficient release time. The decrease in cathodic and anodic kinetics, along with the improved corrosion resistance, show a dual synergistic corrosion inhibition of the NaNO2 loaded colophony MC